Magnesiothermic Reduction‐Enabled Synthesis of Si−Ge Alloy Nanoparticles with a Canyon‐Like Surface Structure for Li−Ion Battery. Issue 19 (26th July 2018) - Ahn, Jihoon; Kim, Bokyung; Jang, Gyumin; Moon, Jooho
Abstract: A new strategy is proposed to synthesize a Si−Ge alloy nanomaterial for a Li‐ion battery anode. Magnesiothermic reduction of the SiO2 −GeO2 composite parent material could provide a nanostructured Si−Ge alloy material with unique canyon‐like surface porosity. The nanostructure of Si−Ge alloys could be intentionally controlled and the resulting canyon‐like porous Si−Ge nanoparticle could be successfully utilized as an anode material, achieving satisfactory cell performance. The proposed synthetic approach can potentially scale‐up the production of Si−Ge alloy nanomaterial. Abstract : Grand Canyon : Highly porous Si−Ge nanoparticles with a canyon‐like surface structure are synthesized through the magnesiothermic reduction of nanostructured SiO2 −GeO2, leading to satisfactory cell performance when used as a Li‐ion battery anode.